Cover Picture: Local Structure Study of Lanthanide Elements by X‐Ray Absorption Near Edge Structure Spectroscopy (Chem. Rec. 7/2019). Issue 7 (16th July 2019) - Asakura, Hiroyuki; Hosokawa, Saburo; Teramura, Kentaro; Tanaka, Tsunehiro
Abstract : The cover picture shows a schematic illustration of local structure analysis of lanthanide elements with X‐ray spectroscopy based on synchrotron radiation. See the Personal Account by H. Asakura, S. Hosokawa, K. Teramura, and T. Tanaka (DOI:10.1002/tcr.201800164 ), part of this special issue on Novel Energy Nanomaterials, Catalysts and Surfaces.